2016
DOI: 10.1073/pnas.1606044113
|View full text |Cite
|
Sign up to set email alerts
|

Atomic lattice disorder in charge-density-wave phases of exfoliated dichalcogenides (1T-TaS 2 )

Abstract: Charge-density waves (CDWs) and their concomitant periodic lattice distortions (PLDs) govern the electronic properties in several layered transition-metal dichalcogenides. In particular, 1T-TaS 2 undergoes a metal-to-insulator phase transition as the PLD becomes commensurate with the crystal lattice. Here we directly image PLDs of the nearly commensurate (NC) and commensurate (C) phases in thin, exfoliated 1T-TaS 2 using atomic resolution scanning transmission electron microscopy at room and cryogenic temperat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
89
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 39 publications
8
89
0
1
Order By: Relevance
“…The electronic charge density, a scalar quantity and a natural order parameter of a CDW, is normally assumed to be linearly coupled to the longitudinal PLD, with the ordered CDW period an integral or fractional multiple of the period of the atomic lattice or the PLD. Such a situation could also arise due to planar defects such as stacking faults [19,20], as is likely to be the case in our samples, given the large changes in lattice constants and phonon frequencies in the 0.2x0.3 region.…”
Section: Selected Area Electron Diffractionmentioning
confidence: 85%
“…The electronic charge density, a scalar quantity and a natural order parameter of a CDW, is normally assumed to be linearly coupled to the longitudinal PLD, with the ordered CDW period an integral or fractional multiple of the period of the atomic lattice or the PLD. Such a situation could also arise due to planar defects such as stacking faults [19,20], as is likely to be the case in our samples, given the large changes in lattice constants and phonon frequencies in the 0.2x0.3 region.…”
Section: Selected Area Electron Diffractionmentioning
confidence: 85%
“…There is a possibility that the properties differ from those in higher layers (bulks). [13][14][15] There has been a recent debate on whether the commensurate CDW phase exists in ultrathin films of 1T-TaS 2 . [16][17][18][19][20] However, the samples considered in these studies either contain a substrate or interacts with the surrounding environment, which inevitably alter the properties of the material.…”
Section: Introductionmentioning
confidence: 99%
“…Prior work has shown that exfoliated 1T-TaS 2 may contain stacking disorder but not vacancies or other point defects that can act as charge trapping sites [18]. Thus, electronhole pairs created during irradiation can readily recombine, greatly reducing the charge yield within the 1T-TaS 2 .…”
Section: Discussionmentioning
confidence: 99%